Case Report: Rhabdomyolysis secondary to vildagliptin overdose in a suicidal attempt: A case report and brief literature review - Tang, Zhijia; Fan, Xiaofang; Feng, Zhen; Han, Bing; Guo, Nan (Frontiers in Pharmacology, 2022)
Rhabdomyolysis is a life-threatening syndrome associated with direct or indirect muscle damage that is rarely reported with dipeptidyl peptidase (DPP)-4 inhibitors. Here we presented a case in which a 58-year-old female suffered from severe swelling and pain in bilateral lower limbs and oliguria after a suicidal vildagliptin overdose. Drug-induced rhabdomyolysis and drug-induced liver injury were diagnosed based on laboratory and radiological findings. The patient was treated with fluid resuscitation, insulin, electrolyte replacement, diuretics, urine alkalizing agents, anticoagulants, antioxidants, and 24-hour bedside ECG monitoring and suicide prevention. After 20 days of hospitalization and close monitoring, the patient was discharged without sequelae. Risk factors, diagnostic criteria, disease mechanisms, and outcomes were also discussed. This case illustrated that overdose of oral anti-diabetic medications may result in clinically significant adverse events, such as rhabdomyolysis in this case with a DPP-4 inhibitor. Although the incidence is low, special attention should be paid to intentional or accidental exposure to anti-diabetic medications during suicide attempts, especially in depressed patients with diabetes.